Isolation, Characterization and Antibacterial Activities of Lactic Acid Bacteria Isolated From Batak's Special Food "Dali Ni Horbo” - Nasution, Muhammad Hasan Basri; Ramadhani, Shafira; Fachrial, Edy (Jurnal Natur Indonesia, 2020)
Lactic Acid Bacteria (LAB) are gram-positive bacteria that are rod or round in shape, do not form spores, and do not have cytochromes. LAB can be isolated from fermented food products. LAB is useful to inhibit the growth of pathogenic bacteria so that they are potential antibacterial sources. The purpose of this study was to isolate LAB from the traditional food Dali Ni Horbo, continued with characterization, antimicrobial testing, and sensitivity testing towards several antibiotics. From the results of the study, the number of colonies obtained was 2.4 x 107 CFU/mL. 6 isolates were randomly selected, coded as isolates UPDH1, UPDH2, UPDH3, UPDH4, UPDH5, UPDH6, respectively. Biochemical characterization showed that the isolates were gram-positive and catalase-negative bacteria.  Results of antibiotic sensitivity testing using 6 antibiotics, namely amoxicillin (AML), erythromycin (E), oxacillin (OX), ofloxacin (OFX), cefotaxime (CTX), and gentamicin (CN), showed that all the isolates were resistant to CTX. The UPDH1 isolate was resistant to AML and OX. The UPDH3, UPDH5, and UPDH6 isolates were resistant to AML, and the UPDH4 isolate was resistant to E, OFX, CTX, CN, and OX. Antimicrobial tests used the disk diffusion method against Escherichia coli and Staphylococcus aureus. The UPDH2 isolate, gave an inhibition zone of 6.7 mm, and UPDH5 and UPDH6 gave inhibition zones of 7.6 mm and 8.5 mm respectively, against E. coli. Microbial inhibition tests against S. aureus by UPDH1, UPDH2, UPDH5 and UPDH6 gave inhibition zones of 13.5 mm, 9.0 mm, 12.1 mm and 12 mm respectively. From the results in this research it can be concluded that the traditional food Dali Ni Horbo is a potential source of probiotics.